High-yield preparation of a zwitterionically charged chitin nanofiber and its application in a doubly pH-responsive Pickering emulsion. Issue 15 (17th July 2017) - Pang, Kai; Ding, Beibei; Liu, Xiaoting; Wu, Hao; Duan, Yongxin; Zhang, Jianming
Abstract : A rapid and high-yield (up to 85%) preparation of a zwitterionic chitin nanofiber (DE-CO-ChNF) has been demonstrated. Abstract : Novel zwitterionic chitin nanofibers (ChNFs) decorated with both cationic (NH3 + ) and anionic (COO − ) groups on the surface have broad applications in various environments. Herein, we demonstrate a rapid and high-yield (up to 85%) synthesis of a zwitterionic ChNF by the combination of partial deacetylation and oxidation using the TEMPO/NaClO2 /NaClO system. Meanwhile, we present the potential application of a bio-based ChNF as an environmentally and doubly pH-responsive Pickering emulsifier to replace conventional pH-responsive Pickering emulsifiers such as inorganic nanoparticles or grafted polymers. This high yield preparation achieved by our method will be in favor of the large-scale applications of ChNFs.